A Subset of Tumor-Derived Mutant Forms of p53 Down-Regulate p63 and p73 through a Direct Interaction with the p53 Core Domain - Gaiddon, C. (American Society for Microbiology, 2001)
The p53 protein is related by sequence homology and function to the products of two other genes, p63 and p73, that each encode several isoforms. We and others have discovered previously that certain tumor-derived mutants of p53 can associate and inhibit transcriptional activation by the α and β isoforms of p73. In this study we have extended these observations to show that in transfected cells a number of mutant p53 proteins could bind and down-regulate several isoforms not only of p73 (p73α, -β, -γ, and -δ) but also of p63 (p63α and -γ; ΔNp63α and -γ). Moreover, a correlation existed between the efficiency of p53 binding and the inhibition of p63 or p73 function. We also found that wild-type p63 and p73 interact efficiently with each other when coexpressed in mammalian cells. The interaction between p53 mutants and p63 or p73 was confirmed in a physiological setting by examining tumor cell lines that endogenously express these proteins. We also demonstrated that purified p53 and p73 proteins interact directly and that the p53 core domain, but not the tetramerization domain, mediates this interaction. Using a monoclonal antibody (PAb240) that recognizes an epitope within the core domain of a subset of p53 mutants, we found a correlation between the ability of p53 proteins to be immunoprecipitated by this antibody and their ability to interact with p73 or p63 in vitro and in transfected cells. Based on these results and those of others, we propose that interactions between the members of the p53 family are likely to be widespread and may account in some cases for the ability of tumor-derived p53 mutants to promote tumorigenesis.